Performance Characteristics of A Simulated Hybrid Solar-Photovoltaic-Thermoelectric System for Renewable and Direct Power Generation Applications (Journal of Solar Energy Research Updates, 2021)
Advanced nonconventional renewable and alternative green energy technologies which are used for generation of electrical power have shown real promise and received renewed interest in recent years due to an increasing concern of environmental issues of greenhouse gas emissions, air pollution, and the limitations and conservation of natural energy resources. Solar-photovoltaic (PV) systems directly convert renewable solar energy into green electrical energy. However, their power production and efficiencies tend to decrease when operating at relatively higher temperatures. Therefore, reducing the temperature of PV modules using efficient cooling methods would improve their performances. Thermoelectric power generation (TEG) technology could be used to convert a portion of the waste-heat energy dissipated from PV systems, thus cooling them, and at the same time generates extra power. Hence, hybrid photovoltaic-thermoelectric power generation (HPV-TEG) systems integrate TEG modules with a PV module to form a more efficient power generation system. The main objective of this paper is to investigate the viability and performance characteristics of a hybrid HPV-TEG through detailed lab-simulated tests. Experimental results and in thermal images showed that the HPV-TEG system was able to generate more DC power than the solo PV system while operating at higher irradiance intensities and lower TEG’s inlet coolant temperature. At the irradiance of 615W/m2, the power generation from the hybrid HPV-TEG system increased by 4.1% compared to the solo PV system. The results also indicated that when the irradiance was increased to 750W/m2, the power generated from the hybrid system increased to approximately 8.6% higher than the power generated from the solo PV system at the same irradiance. The integration of the concentrators in the hybrid PV system increased the maximum power point by 23.3% compared to the hybrid PV system without concentrators.